Corporate Reputation Management of Selected Financial Institutions in FCT, Abuja - David, Akai Hannah; Akpede, K. S.; Kente, J. S. (Lembaga Yasin AlSys, 2025)
This study investigated corporate reputation management in two financial institutions—First Bank and Guarantee Trust Bank (GTBank)—within the Federal Capital Territory (FCT), Abuja. The objective was to assess how public relations (PR) strategies, particularly social media use, contribute to reputation building and information management in these banks. A survey research design was adopted. Findings indicate that most respondents maintain social media accounts and that both banks deploy PR strategies for reputation management, including traditional channels (news magazines, online news magazines, and News Tit-Bits) and social media platforms (Facebook, Twitter, Instagram, among others). The use of these platforms has increased awareness of First Bank and GTBank in Abuja and fostered trust, acceptability, patronage, and believability of updates. The PR departments of both banks appear to be maximizing social media as a channel for communicating with target audiences, supporting counseling, information management, crisis management, and media and community relations. The study concludes that social media use by the banks’ PR departments has been effective in information management and in enhancing the image and reputation of the banks to some extent. The findings imply that bank management should recognize the strategic importance of PR units and ensure adequate funding to enable them to fulfill their responsibilities and activities effectively.